Anisotropic Hypoplastic Model Considering the Relation between Fabric Tensor and Anisotropic Parameters - Yong-Gwang Jong; Zixuan Chen; YongMin Ma; Yang Liu (Geofluids)
The fabric anisotropy and anisotropic parameters have great effect on the mechanical property of sand. Based on the existing anisotropic model, a modified anisotropic hypoplastic model is developed by incorporating the relation between fabric tensor and anisotropic parameters into the nonlinear part of the constitutive model. The applicability of the improved anisotropic hypoplastic model is validated by comparing with the existing model and experimental data. As a result, it is found that the modified model can well predict the mechanical response of anisotropic sand.